Penilaian Visual Lanskap Objek Daya Tarik Wisata Alam dengan Menggunakan Metode ADO-ODTWA di Obyek Wisata Curug Muncar - Rahayu, Kinanthi; Winastuti Dwi Atmanto (Direktorat Pengabdian kepada Masyarakat, 2024)
This article aims to assess the visual potential of the landscape of natural tourism objects in Curug Muncar. The assessment was carried out using the Analysis Method of Operational Areas for Natural Tourism Objects and Attractions (ADO- ODTWA). This method focuses on the quality of beauty (scenic views) or the visual quality of the landscape in order to find out the potential that can be developed and improve the shortcomingsof the Curug Muncar natural tourism object. The aspects assessed on the visual potential of Curug Muncar landscape include natural beauty, uniqueness of natural resources, prominent natural resource potential, integrity of natural resources, utilization of natural resources, types of natural tourism activities, cleanliness of air and location, and vulnerability of the area. Based on the results of the assessment of the visual potential of the landscape, a score of 920 was obtained which was included in the sufficient or moderate category to be developed as a nature tourism with a feasibility level of 64%. From the assessment, suggestions were also obtained for management, namely by developing other types of natural tourism in Curug Muncar such as camping, birdwatching, natural education facilities and extreme sports paragliding.